KSDE CHILD NUTRITION AND WELLNESS: ADMINISTRATION OF CHILD NUTRITION PROGRAMS - Kuckelman, Holly (My University, 2017)
This report presents a detailed field experience with the Kansas State Department of Education (KSDE) Child Nutrition and Wellness division. Work on federally funded, state administered child nutrition programs will be discussed. Completed projects include development of Child and Adult Care Food Program (CACFP) and Summer Food Service Program (SFSP) outreach flyers and articles explaining benefits and requirements of these programs; creation of a SFSP cycle menu to be used by sponsors with limited resource serving sites; development and implementation of educational SFSP activities aimed at increasing program participation; and presentation of the updated CACFP meal pattern to K-State Research and Extension Family and Consumer Sciences Agents at their annual training. The experience of being a Child Nutrition and Wellness intern within KSDE deepened my understanding of public health program administration. Working directly with the Child Nutrition and Wellness director, Ms. Cheryl Johnson, MS, RD, LD, along with assistant directors, consultants, other government departments, and private organizations provided hands-on experience in program development, implementation, management, and evaluation, which, when combined with my MPH core coursework, strengthened my ability to be successful in my future public health career.
Keywords: Kansas State Department of Education; Child Nutrition and Wellness; Child Nutrition Programs; CACFP; SFSP